Hedonism on the Shifting Ideas of the Characters in The Film The Tinder Swindler and The Great Gatsby: A Comparative Study - Yusuf, Putri; Nasrum; Dahlan (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study compares the representation of hedonism and the shift in thinking of characters in the films The Tinder Swindler (2022) and The Great Gatsby (2013). This study uses a qualitative descriptive method using the theory of hedonism by Epicurus (341-270 BC) as the basis for analysis. This study found that in The Tinder Swindler, hedonism is used as a tool of manipulation in the digital era, while in The Great Gatsby, hedonism reflects the search for happiness that ends tragically. Simon Leviev's character does not experience a change in thinking, still holding on to his hedonistic life principles even though he is caught, while Jay Gatsby experiences the realization that wealth cannot repeat the past. A comparison of social contexts shows that The Tinder Swindler reflects the culture of imagery on social media, while The Great Gatsby reflects the excesses of capitalism in the Roaring Twenties era. The conclusion of this study emphasizes that excessive hedonism can lead to destruction, both in the modern world and in a historical context. This study reminds us that the search for happiness through material things often ends in emptiness. Thus, this study reveals that not all forms of hedonism lead to true happiness, especially when based on the illusion of wealth and social image